Were metabolic and other chronic diseases the driven onset epidemic forces of COVID-19 in Mexico? - Acevedo-Sánchez, Gerardo; Mora-Aguilera, Gustavo; Coria-Contreras, Juan J.; Álvarez-Maya, Ikuri (Frontiers in Public Health, 2023)
The underline hypothesis of this work was that SARS-CoV-2 can infect individuals regardless health condition, sex, and age in opposition to classical epidemiological assumption of an identifiable susceptible subpopulation for epidemic development. To address this issue, a population cohort with 24.4 million metadata associated to 226089 official RT-qPCR positive and 283450 negative cases, including 27769 deceased, linked putatively to B.1. and B.1.1. SARS-CoV-2 lineages were analyzed. The analysis baseline was to determine infection and mortality structure of the diseased cohort at onset-exponential phase of first epidemic wave in Mexico under assumption of limited herd immunity. Nonchronic diseased individuals (NOCDs) were compared with those exhibiting at least one of 10 chronic diseases (CDs) adjusted by age and sex. Risk factors for infection and mortality were estimated with classification and regression tree (CART), and cluster analysis based on Spearman's matrix of rho-values in RStudio®, complemented with two proposed mortality indices. SARS-CoV-2 infection was independent of health condition (52.8% NOCD vs 47.2% CDs; p=0.001-0.009) but influenced age greater than 46 in one risk analyses scenario (p<0.001). Sex contributed 9.7% to overall risk. The independent effect was supported by the health structure of negative cases with a similar tendency but a higher proportion of NOCDs (61.4%, p=0.007). The infection probability in individuals with one CD was determined by the disease type and age, which was higher in those older individuals (≥56-years) exhibiting diabetes (12.3%, cp=0.0006), hypertension (10.1%, cp<0.0001), and obesity (7.8%, cp=0.001). In contrast, the mortality risk was heavily influenced by CD conditioned by sex and age, accounting for 72.3% of total deaths (p=0.001-0.008). Significant risk mortality (48%) was comprised of ≥56-year-old woman and man (w, m) with diabetes (19% w and 27.9% m, cp<0.0004), hypertension (11.5% w, cp=0.0001), and CKD (3.5% w and 5.3% m, cp=0.0009). Older people with diabetes and hypertension comorbidity increased the risk to 60.5% (p=0.001). Based on a mortality weighted index, women were more vulnerable with preexisting metabolic or cardiovascular diseases. These findings support our hypothesis and justify the need for surveillance systems at communitarian level. This is the first study addressing this fundamental epidemiological question.